Prevalence and determinants of self-medication with antibiotics in high and low-income areas within Cairo - Hassan, Shaymaa Mohamed (AUC Knowledge Fountain, 2018)
Antimicrobial Resistance (AMR) is currently a global threat, and one of the reasons for increasing AMR rates is antibiotics overuse. Antibiotics overuse is not only due to physician prescriptions -although that is also high- but also because of self-medication with antibiotics (SMA). SMA varies across countries and populations depending on multiple factors and among them is the socioeconomic status. Socioeconomic disparities have been linked to SMA rates. In Egypt, namely Cairo, little data is available regarding SMA or surveillance of antibiotic consumption. The aims of this study were to a) estimate and compare the prevalence of SMA in two socioeconomically different areas in Cairo (high and low-income) b) identify determinants associated with SMA and c) Identify the types of antibiotics used the most. Results showed that SMA was four times more prevalent in low-income area compared to the high-income area (p = 0.00). However, total consumption of antibiotics per family, whether by SMA or prescription, was significantly higher (p = 0.037) in the high-income area. Amoxiciillin was found to be the most consumed antibiotic in both areas Maadi (60.7%) and Shagret Mariam 48.2%. The main reason for SMA in both areas was having previous experience with similar symptoms. Other reasons differed between low income areas (cost of physician) and higher income areas (saving time). Income and education were among the factors related to SMA whereas with lower education and low-income area, there was higher rates of SMA. Further research is recommended to understand SMA behavior and its' socioeconomic determinants, in order to address interventions for regulating antibiotic use.